Ethnomedicine of the Gadabas, a primitive tribe of Visakhapatnam district, Andhra Pradesh - Seetharami Reddi; O. Aniel Kumar, J. Koteswara Rao*, J. Suneetha, T.V.V. (International Multidisciplinary Research Journal, 2011)
<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;">Though there are a good number of publications on ethnobotany publications on a particular tribe are not many necessitating the present study. The paper enumerates 62 medicinal plant species belonging to 61 genera and 43 families used for ethnomedicinal purposes by the Gadaba primitive tribe of Visakhapatnam district, Andhra Pradesh. Visakhapatnam district with an area of 11, 161 Km2 (4.1% of the area of the state) is one of the north eastern coastal districts of Andhra Pradesh. The study area lies between 17Ã‚Âº-34’ 11" and 18Ã‚Âº-32’ 57" northern latitude and 18Ã‚Âº-51’ 49" and 83Ã‚Âº-16’ 9" in eastern longitude. The entire agency track covers 6, 298 Km2 i. e., 56.4% of the total geographical area of the district.